Sustainable diet of people of Cireundeu Village as Social Studies learning resources - Fitriyani, Anindyta; Sundawa, Dadang; Nur, Muhammad (Universitas Negeri Yogyakarta, 2025)
A sustainable diet is a dietary approach rooted in sustainability principles, considering health, socio-economic, and ecological factors. The local community in Indonesia, specifically in the Cireundeu Traditional Village, Cimahi City, also practices a sustainable diet. Cassava rice is the primary sustenance of the inhabitants of this village. This investigation aims to evaluate the sustainable diet conditions of the Cireundeu Indigenous Village community and its benefits for social studies learning resources. The method employed is descriptive qualitative. The data collection techniques employed in this research are observation, interviews, and literature study, which are analyzed using data analysis techniques such as data reduction, data presentation, and conclusion drawing. The research findings indicate that the local wisdom of consuming cassava rice contains components of a sustainable diet. The relevance of the Cireundeu Indigenous Village's sustainable diet as a learning resource for social studies can be assessed through the themes and traditions of social studies education. The sustainable diet of the Cireundeu community can also be applied to various relevant themes or subjects in social studies, including the utilization of natural resources, sustainable development goals, economic activities, local wisdom, and economic policies during colonialism. Consequently, the sustainable diet of the Cireundeu Traditional Community is highly pertinent when employed as a learning resource for social studies.